Five new ways to use nursing research at the point-of-care: tips for fast search, specific and highly relevant - Cruz, Isabel CF da (Online Brazilian Journal of Nursing, 2010)
HTML clipboard <!– span.MsoEndnoteReference vertical-align:super span.subhead1 font-family:Verdana; font-weight:bold span.MsoFootnoteReference vertical-align:super table.MsoTableGrid border:1.0pt solid windowtext; font-size:10.0pt; font-family:"Times New Roman" li.MsoNormal mso-style-parent:""; margin-bottom:.0001pt; font-size:12.0pt; font-family:"Times New Roman"; margin-left:0cm; margin-right:0cm; margin-top:0cm table.MsoTable3DFx2 font-size:10.0pt; font-family:"Times New Roman"; table.MsoTableColorful1 border:1.5pt solid teal; font-size:10.0pt; font-family:"Times New Roman"; color:white; table.MsoTableClassic2 border-top:1.5pt solid black; border-left:medium none; border-bottom:1.5pt solid black; border-right:medium none; font-size:10.0pt; font-family:"Times New Roman"; table.MsoTableColorful2 border-left:medium none; border-right:medium none; border-top:medium none; border-bottom:1.5pt solid black; font-size:10.0pt; font-family:"Times New Roman"; –> It is imperative to develop skills to integrate research and patient care for nurses through the access to the research findings at internet databases.